2011
DOI: 10.1161/circulationaha.110.010769
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mathematical Modeling to Compare and Predict Hemodynamic Effects Between Hybrid and Surgical Norwood Palliations for Hypoplastic Left Heart Syndrome

Abstract: Background-Combining bilateral pulmonary artery banding with arterial duct stenting, the hybrid approach achieves stage 1 palliation for hypoplastic left heart syndrome with different flow characteristics than those after the surgical Norwood procedures. Accordingly, we used computational modeling to assess some of these differences, including influence on systemic and cerebral oxygen deliveries. Methods and Results-A 3-dimensional computational model of hybrid palliation was developed by the finite volume met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 25 publications
0
56
1
1
Order By: Relevance
“…Conversely, pathology developments can depend on abnormal hemodynamics, such as in the absence of a functioning valve, as will be the case in this work. Computer hemodynamic simulations provide a tool to predict hemodynamic changes due to surgical repair (Vignon-Clementel et al, 2010b), explore different scenarios for treatment (see, e.g., (Hsia et al, 2011;Yang et al, 2011)), non-invasively compute indices that are otherwise invasively measured such as fractional flow reserve (FFR) (Koo et al, 2011), and design artificial devices or conduits that are subject to blood flow (see, e.g., (Prasad et al, 2011;Pant et al, 2011)). …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, pathology developments can depend on abnormal hemodynamics, such as in the absence of a functioning valve, as will be the case in this work. Computer hemodynamic simulations provide a tool to predict hemodynamic changes due to surgical repair (Vignon-Clementel et al, 2010b), explore different scenarios for treatment (see, e.g., (Hsia et al, 2011;Yang et al, 2011)), non-invasively compute indices that are otherwise invasively measured such as fractional flow reserve (FFR) (Koo et al, 2011), and design artificial devices or conduits that are subject to blood flow (see, e.g., (Prasad et al, 2011;Pant et al, 2011)). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the demonstration of the cumulative effect of the other risk factors on transplant-free survival in addition to shunt (Figure 30) suggests that the physiology of patients with a BT shunt and RVPA conduit is fragile. The hypothesis that poor coronary perfusion associated with the diastolic run off caused by a BT shunt which leads to a poor myocardia perfusion ( Figure 34) (Bradley et al 2004;Ghanayem et al 2006;Donnelly et al 1998;DeCampli et al 2013;Hsia et al 2011), is …”
Section: Effect Of Shunt Type In Our Right Ventricular Dysfunction Comentioning
confidence: 99%
“…In reality, both shunt types can cause or potentiate the effect of ventricular dysfunction. The BT shunt allows for continuous flow into the pulmonary circulation, which leads to diastolic run off (Hsia et al 2011). A diastolic run off means that flow to the pulmonary arteries continues in diastole instead of only occurring in systole ( figure 34 and 35).…”
Section: The Physiology Associated With the Bt Shuntmentioning
confidence: 99%
“…The study by Hsia [42] reported the application of a 0D-3D multi-scale model to predict the differences in hemodynamic impact between hybrid and surgical Norwood palliations for hypoplastic left heart syndrome. In the study, a 3D computational fluid dynamics model of either the Norwood or the hybrid procedure was coupled to a lumped parameter description of the entire circulation.…”
Section: Patient-specific Modeling and Clinical Applicationsmentioning
confidence: 99%
“…The micro-hemodynamics in the micro-vascular system (MVS) covers a widely heterogeneous complex network of the capillaries connecting the arteriovenous system, from the cardiovascular system as a whole down to blood cells and LSA indicates the subclavian artery, RSA right subclavian artery, LCA left carotid artery, and RCA right carotid artery [42] single cells of the vessel. Modeling studies in MVS have been done mostly at different scales with the one-dimensional (1D) micro-circulatory models on non-pulsatile and pulsatile flows, the behaviour of shape and deformation of single RBC, as well as the mechanical interaction between single RBC and plasma, and RBC to RBC interaction via plasma fluid, and [42] sub-cellular models associated with events like deformation, migration and division.…”
Section: Overviewmentioning
confidence: 99%